Law Enforcement Against The Crime Of Vandalism In The Jurisdiction Of The Medan Polrestabes - Alam Pratama Harahap; Dani Sintara (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Vandalism is closely related to social problems in general (social panthology), the causes of which can occur due to economic, political, or even smaller scope factors, namely the family. The subjects of this vandalism are all people involved in the culture of destruction, destruction carried out together by a group or individual. Their targets are usually in general public spaces such as bus stops, traffic signs, highway signs, walls, and so on. In Indonesia vandalime is considered a form of activity that is often ignored by society because it is considered a form of petty mischief that has little impact on life. However, vandalism is a serious problem , if it is not handled quickly and appropriately it will become a big problem. The problem in this research regarding law enforcement against acts of vandalism is that there are still things that deviate from the law , for example the absence of complete assignment letters when carrying out investigations. The aim of this research is to determine a series of acts of vandalism. The method used in this research is an empirical juridical method, namely a case study of vandalism in the jurisdiction of the Medan Police.